Dinamika Implementasi PPh Pasal 23 pada Sektor Usaha Kecil dan Menengah (UKM): Studi Fenomenologi di Kota Medan - Putri Norlayli Mustakim; Uci Fadillah; Siti Khairani Arfandi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study analyzes the dynamics of implementing Income Tax Article 23 (PPh Pasal 23) among Small and Medium Enterprises (SMEs) in Medan City using a phenomenological approach. Data were collected through in-depth interviews with 12 SME owners who had fulfilled PPh Pasal 23 obligations for at least two years. Four critical themes were identified: (1) limited understanding of tax objects and mechanisms, (2) administrative challenges in digital systems (e-billing and e-SPT), (3) perceptions of fiscal injustice due to double taxation and inequality with informal sector competitors, and (4) the role of external pressures from business partners in driving compliance. The research highlights the disparity between regulatory design and SMEs' adaptive capacity, as well as the psychosocial complexity in internalizing tax obligations. Policy implications emphasize the need for contextual education, simplified administrative systems, equitable law enforcement, and multi-stakeholder collaboration to build an inclusive compliance ecosystem.